Pengaruh inovasi produk terhadap minat beli pada usaha tekat tiga dara di Kota Pekanbaru - Siti Viona; Rosmayani Rosmayani (Pelantar Press, 2021)
The research conducted by the author aims to determine the effect of the Product Innovation variable on the Buying Interest variable in the Tekat Tiga Dara business in Pekanbaru City, the phenomena raised include making new innovations to improve product quality, product innovation both in terms of increasing prices and values. use the product in order to create the features of the products sold, prioritizing Malay characteristics, The level of consumer buying interest in Tekat Tiga Dara products occurs because of the attractiveness of each unique product, and consumers tend to buy Tekat Tiga Dara products because of the desire for new product innovations. resulting from. This type of research is descriptive with quantitative methods. The sampling technique used incidental sampling technique with a total sample of 50 respondents, the data used in the study were obtained through observation, interviews, questionnaires and literature studies, the types of data sources used in this study were primary data and secondary data then data analysis techniques used in this study This research includes Validity Test, Reliability Test, T Test, Simple Coefficient of Determination, Statistical Hypothesis, and Simple Linear Regression using SPSS v.22. For the results of the tests carried out, the results showed that the product innovation variable affected buying interest in the business of three virgins in the city of Pekanbaru.